Preparation method and application of anti-hepatic fibrosis nano-drug

By preparing iron-sulfide-artemisinin nano-complexes, the problem of not effectively treatment of liver fibrosis in the existing technology has been solved, and the effect of effectively killing fibrosis cells in the liver fibrosis environment is achieved.

CN119367394AActive Publication Date: 2025-01-28SHANDONG PROVINCIAL HOSPITAL AFFILIATED TO SHANDONG FIRST MEDICAL UNIVERSITY (SHANDONG PROVINCIAL HOSPITAL)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411587620.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

There is no relevant report on the treatment of liver fibrosis with iron sulfide-loaded artemisinin, which is difficult to effectively solve the treatment problem of liver fibrosis.

Method used

By mixing the sulfate, sodium citrate, sodium and ethylene glycol to form iron sulfide nano tablets, combined with artemisinin, to prepare anti-liver fibrosis-nano-nano composite.

Benefits of technology

The nano -complex is degraded in the liver fibrosis environment, released iron ion and artemisinin, and enhances the treatment effect. By interfere with the oxidation and reduction balance and calcium ion channel of fibrosis cells, inhibit cell proliferation, and significantly kills fibrosis cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367394A_ABST
    Figure CN119367394A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological medicine, in particular to a preparation method and application of an anti-hepatic fibrosis nano-drug. Ammonium ferrous sulfate, trisodium citrate and ethylene glycol are mixed, and a solution A is obtained; mixing the solution A with a polyethyleneimine solution to obtain a solution B; mixing the solution B with a thioacetamide solution to obtain a solution C; mixing the solution C with triethanolamine, and reacting to obtain iron sulfide nanosheets; the preparation method comprises the following steps: mixing an iron sulfide nanosheet with SH-PEG-NH2 and absolute ethyl alcohol to obtain FP; the FP is mixed with artemisinin and absolute ethyl alcohol, and the anti-hepatic fibrosis nano-drug is obtained. The FPA synthesis method is simple and high in operability; the product is stable and has repeatability; fPA has good biocompatibility and biodegradability, and responsively degrades high-expression hydrogen peroxide after entering a hepatic fibrosis microenvironment, so that the change of the hepatic fibrosis microenvironment is promoted, and further apoptosis is caused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedicine technology, and in particular to a preparation method and application of an anti-liver fibrosis nano drug. Background Art

[0002] Liver fibrosis is a serious liver disease characterized by excessive connective tissue accumulation in the liver, usually caused by viral hepatitis, long-term alcoholism, and non-alcoholic fatty liver disease. Liver fibrosis can lead to irreversible damage to the structure and function of the liver, and may eventually evolve into cirrhosis and liver failure. This not only reduces the patient's quality of life, but also increases the risk of liver cancer. Patients with cirrhosis often face serious complications such as ascites, esophageal variceal bleeding, and hepatic encephalopathy, leading to a higher mortality rate. Therefore, early intervention and effective treatment are crucial to improving prognosis.

[0003] In recent years, nanomaterials have developed rapidly in the medical field, especially showing great potential in the diagnosis and treatment of diseases. Nanomaterials are ideal for drug delivery systems due to their unique physicochemical properties, such as responsive release, particle size suitable for endocytosis, and easy surface functionalization. Nanomaterials have significant advantages in the treatment of liver fibrosis. First, nanomaterials are easily enriched in the liver because the liver is the main detoxification organ of the human body and has a rich reticuloendothelial system. Second, due to the increase in metabolites during chronic inflammation and extracellular matrix remodeling, especially the increase in lactic acid and other organic acids, the microenvironment of liver fibrosis cells is more acidic than that of normal cells. This acidic environment prompts the responsive nanomaterials to degrade and release active ingredients, thereby enhancing the therapeutic effect and reducing side effects.

[0004] There is no related report on the use of iron sulfide loaded with artemisinin to treat liver fibrosis in the prior art. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a preparation method and application of an anti-liver fibrosis nanomedicine. The preparation method provided by the present invention is simple, highly operable, causes strong oxidative stress, has a strong killing effect on liver fibrosis cells, and is conducive to clinical application.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing an anti-liver fibrosis nanomedicine, comprising the following steps: 1) Mix ammonium ferrous sulfate, trisodium citrate and ethylene glycol to obtain solution A; 2) mixing the solution A obtained in step 1) with the polyethyleneimine solution to obtain a solution B; 3) mixing the solution B obtained in step 2) with the thioacetamide solution to obtain a solution C; 4) mixing the solution C obtained in step 3) with triethanolamine and reacting the mixture to obtain iron sulfide nanosheets; 5) mixing the iron sulfide nanosheets obtained in step 4) with mercapto-polyethylene glycol-amino and anhydrous ethanol to obtain polyethylene glycol-coated iron sulfide nanosheets; 6) Mixing the polyethylene glycol-coated iron sulfide nanosheets obtained in step 5) with artemisinin and anhydrous ethanol to obtain an anti-liver fibrosis nanomedicine.

[0007] Preferably, in step 1), the volume ratio of the molar ratio of ammonium ferrous sulfate, the molar ratio of trisodium citrate and ethylene glycol is 0.6 mmol:0.2 mmol:15 mL.

[0008] Preferably, the components of the polyethyleneimine solution in step 2) include polyethyleneimine and ethylene glycol, and the mass ratio of the polyethyleneimine to the volume of ethylene glycol is 500 mg:5 mL; The molar ratio of the volume of the polyethyleneimine solution to the ammonium ferrous sulfate is 5 mL:0.6 mmol; The mixing conditions include: stirring at 500 rpm for 2 hours.

[0009] Preferably, the components of the thioacetamide solution in step 3) include thioacetamide and ethylene glycol, and the mass ratio of thioacetamide to ethylene glycol is 56.3475 mg:15 mL; The mixing is carried out under stirring, and the stirring time is 10 minutes; The volume ratio of the thioacetamide solution to the polyethyleneimine solution is 3:1.

[0010] Preferably, in step 4), the volume ratio of triethanolamine to thioacetamide solution is 0.5:15; The mixing is carried out under stirring, and the stirring time is 10 minutes; The reaction conditions include: temperature of 200°C and time of 4h; The reaction is followed by centrifugation and washing to obtain iron sulfide nanosheets; the centrifugation conditions include: a rotation speed of 14000 rpm and a time of 10 minutes; and washing with anhydrous ethanol for 3 times.

[0011] Preferably, in step 5), the volume ratio of the mass of the iron sulfide nanosheets to the mass of the mercapto-polyethylene glycol-amino group and anhydrous ethanol is 1 mg:1 mg:2 mL.

[0012] Preferably, the mixing in step 5) is carried out under stirring, and the stirring time is 6 hours; The stirring is followed by centrifugation and washing, wherein the centrifugation conditions include: a rotation speed of 14000 rpm for 10 min; and washing with anhydrous ethanol for 2 times.

[0013] Preferably, in step 6), the volume ratio of the mass of the polyethylene glycol-coated iron sulfide nanosheets to the mass of artemisinin and anhydrous ethanol is 1 mg:1 mg:2 mL; The mixing is carried out under stirring, and the stirring time is 6 hours; The stirring is followed by centrifugation and washing, wherein the centrifugation conditions include: a rotation speed of 14000 rpm for 10 min; and washing with anhydrous ethanol for 2 times.

[0014] The present invention also provides an anti-liver fibrosis nanomedicine prepared by the preparation method described in the above technical scheme.

[0015] The present invention also provides the use of the anti-liver fibrosis nanomedicine described in the above technical solution in the preparation of a drug for treating liver fibrosis.

[0016] The present invention develops an iron sulfide-artemisinin nanocomposite (FPA). The complex degrades in the liver fibrosis environment, releasing iron ions and artemisinin. The ferrous ions in the iron sulfide are reducing, and can synergize with artemisinin in the liver fibrosis microenvironment to enhance the therapeutic effect. Artemisinin, through its reducing properties, combines with iron ions to form a complex with strong reducing ability, which can interfere with the redox balance of fibrotic cells. This interference leads to an increase in the level of oxidative stress in the cells, which in turn affects the viability of the cells. In addition, artemisinin can inhibit calcium ion channels in fibrotic cells, interfere with the normal transport and signal transduction of calcium ions, and hinder the normal function of cells. Artemisinin can also inhibit specific enzymes, such as DNA topoisomerase, prevent DNA replication and transcription, and interfere with the proliferation ability of cells. By inhibiting the cytochrome P450 enzyme system, artemisinin further enhances the killing effect of fibrotic cells.

[0017] Therefore, the iron sulfide-artemisinin nanocomplex has significant potential in the treatment of liver fibrosis, providing a novel and efficient treatment strategy. This nanocomplex selectively destroys fibrotic cells and reduces the accumulation of fibrous tissue, while having little effect on normal cells, showing great potential as a drug for the treatment of liver fibrosis. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0019] Figure 1 This is a transmission electron microscope image of the prepared iron sulfide; Figure 2 Atomic force microscope images of the prepared iron sulfide nanosheets: (left) Atomic force microscope image of the iron sulfide nanosheets and thickness test image, (right) Atomic force microscope electron microscope image of the iron sulfide nanosheets; Figure 3 is the hydrated particle size of the prepared iron sulfide; Figure 4 is the absorbance curve of the prepared iron sulfide with different concentrations; Figure 5 is the absorbance curve of artemisinin at different concentrations; Figure 6 is the concentration-absorbance standard curve of artemisinin in anhydrous ethanol (202 nm); Figure 7 is the drug loading curve of the prepared FPA; Figure 8 The results of in vitro hemolysis test of the prepared FPA nanosheets are shown; Fig. 9 The killing effect of the prepared FPA nanosheets on LX-2 cells (different concentrations); Fig.10 is the consumption of hydrogen peroxide by the prepared FPA nanosheets; Fig.11 is the concentration uptake of the prepared FPA nanosheets; Fig.12 The expression of proteins related to liver fibrosis in different groups. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing an anti-liver fibrosis nanomedicine, comprising the following steps: 1) Mix ammonium ferrous sulfate, trisodium citrate and ethylene glycol to obtain solution A; 2) mixing the solution A obtained in step 1) with the polyethyleneimine solution to obtain a solution B; 3) mixing the solution B obtained in step 2) with the thioacetamide solution to obtain a solution C; 4) mixing the solution C obtained in step 3) with triethanolamine and reacting the mixture to obtain iron sulfide nanosheets; 5) mixing the iron sulfide nanosheets obtained in step 4) with thiol-polyethylene glycol-amino and anhydrous ethanol to obtain polyethylene glycol-modified iron sulfide nanosheets; 6) Mixing the polyethylene glycol-modified iron sulfide nanosheets obtained in step 5) with artemisinin and anhydrous ethanol to obtain an anti-liver fibrosis nanomedicine.

[0021] The present invention mixes ammonium ferrous sulfate, trisodium citrate and ethylene glycol to obtain solution A. In the present invention, the volume ratio of the mole of ammonium ferrous sulfate, the mole of trisodium citrate and the ethylene glycol is preferably 0.6 mmol:0.2 mmol:15 mL.

[0022] The present invention mixes the obtained solution A with a polyethyleneimine solution to obtain a solution B. In the present invention, the components of the polyethyleneimine solution preferably include polyethyleneimine and ethylene glycol, and the mass ratio of the polyethyleneimine to the volume ratio of ethylene glycol is preferably 500 mg: 5 mL. In the present invention, the molar ratio of the volume of the polyethyleneimine solution to ammonium ferrous sulfate is preferably 5 mL: 0.6 mmol. In the present invention, the mixing conditions preferably include: stirring at 500 rpm for 2 h. In the present invention, the polyethyleneimine acts as a surfactant, and the ethylene glycol is a solvent.

[0023] The present invention mixes the obtained solution B with a thioacetamide solution to obtain a solution C. In the present invention, the components of the thioacetamide solution preferably include thioacetamide and ethylene glycol, and the mass of the thioacetamide and the volume ratio of ethylene glycol are preferably 56.3475 mg: 15 mL. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is 10 min. In the present invention, the volume ratio of the thioacetamide solution to the polyethyleneimine solution is preferably 3: 1. In the present invention, the role of the thioacetamide is to provide a sulfur source for iron sulfide.

[0024] The present invention mixes the obtained solution C with triethanolamine and reacts them to obtain iron sulfide nanosheets. In the present invention, the volume ratio of the triethanolamine to the thioacetamide solution is preferably 0.5:15. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is preferably 10 minutes. In the present invention, The reaction conditions preferably include: a temperature of 200°C and a time of 4 hours. In the present invention, the reaction preferably includes centrifugation and washing to obtain iron sulfide nanosheets. In the present invention, the centrifugation conditions preferably include: a rotation speed of 14000 rpm and a time of 10 minutes. In the present invention, the precipitate obtained by centrifugation is preferably washed with anhydrous ethanol for 3 times.

[0025] The present invention mixes the obtained iron sulfide nanosheets with thiol-polyethylene glycol-amino and anhydrous ethanol to obtain polyethylene glycol-modified iron sulfide nanosheets. In the present invention, the mass of the iron sulfide nanosheets to the mass of the thiol-polyethylene glycol-amino and the volume ratio of anhydrous ethanol is preferably 1 mg: 1 mg: 2 mL. In the present invention, the role of the thiol-polyethylene glycol-amino is to improve the biocompatibility of iron sulfide and reduce the toxicity of iron sulfide. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is preferably 6 hours. In the present invention, the stirring is preferably followed by centrifugation and washing, and the centrifugation conditions include: a rotation speed of 14000 rpm and a time of 10 minutes; the present invention preferably uses anhydrous ethanol to wash the precipitate obtained by centrifugation, and the number of washings is 2 times.

[0026] The present invention mixes the obtained polyethylene glycol-modified iron sulfide nanosheets with artemisinin and anhydrous ethanol to obtain an anti-liver fibrosis nanomedicine. In the present invention, the mass of the polyethylene glycol-modified iron sulfide nanosheets and the mass of artemisinin and anhydrous ethanol are preferably in a volume ratio of 1 mg: 1 mg: 2 mL. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is preferably 6 hours. In the present invention, the stirring is preferably followed by centrifugation and washing, and the centrifugation conditions preferably include: a rotation speed of 14000 rpm and a time of 10 minutes; the present invention preferably washes the precipitate obtained by centrifugation with anhydrous ethanol, and the number of washings is 2 times.

[0027] The present invention also provides an anti-liver fibrosis nanomedicine prepared by the preparation method described in the above technical scheme.

[0028] The present invention also provides the use of the anti-liver fibrosis nano drug described in the above technical solution in the preparation of a drug for treating liver fibrosis. The present invention does not specifically limit the dosage form and preparation method of the drug, and those skilled in the art can use the pharmaceutically acceptable dosage form and preparation method of the iron sulfide-artemisinin nanocomposite.

[0029] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention. Embodiment 1:

[0030] A method for preparing an iron sulfide-artemisinin nanocomposite (i.e., an anti-liver fibrosis nanomedicine), comprising the following steps: 1. Preparation of iron sulfide nanosheets: 1) Dissolve 0.6 mmol of ammonium ferrous sulfate and 0.2 mmol of trisodium citrate in 15 mL of ethylene glycol to obtain solution A; 2) Dissolve 500 mg of polyethyleneimine (PEI) in 5 ml of ethylene glycol, add the PEI ethylene glycol solution to the mixed solution, and stir at room temperature and 500 rpm for 2 h to obtain solution B; 3) Dissolve 56.3475 mg of thioacetamide in 15 ml of ethylene glycol, then add to solution B and continue stirring for 10 min to obtain solution C; 4) Add 0.5 ml of triethanolamine to solution C and continue stirring for 10 min. Transfer the mixed solution to a Teflon-lined autoclave and keep it at 200 °C for 24 hours. Centrifuge at 14000 rpm for 10 min, collect, and wash with anhydrous ethanol three times. The product is stored in anhydrous ethanol (FeS nanosheets).

[0031] 2. Take 1 mg of SH-PEG-NH2 and 1 mg of FeS, use 2 ml of anhydrous ethanol as solvent, and stir at room temperature for 6 hours. After stirring, centrifuge at 14000 rpm for 10 minutes, collect, and wash twice with anhydrous ethanol to obtain FP.

[0032] 3. Add 1 mg of FP (based on the mass of iron sulfide) and 1 mg of artemisinin into 2 ml of anhydrous ethanol, stir for 6 hours, then centrifuge at 14,000 rpm for 10 minutes, collect, and wash twice with anhydrous ethanol to obtain an iron sulfide-artemisinin nanocomposite, referred to as FPA.

[0033] Experimental Example 1 Performance Analysis:

[0034] (1) If Figure 1 As shown, take an appropriate amount of iron sulfide, prepare it into a 1 mg / mL solution with anhydrous ethanol, use a pipette to take 10-20 µL and drop it onto a copper grid, dry it to prepare a transmission electron microscopy sample, and observe it with a transmission electron microscope. The results show that the prepared FeS shows a uniform flake shape.

[0035] (2) If Figure 2 As shown, the atomic force microscope image of the prepared two-dimensional iron sulfide nanosheet. The results show that the iron sulfide is in the form of a two-dimensional thin sheet, which is consistent with its transmission electron microscope image. The thickness of the nanosheet is about 2.5nm.

[0036] (3) If Figure 3 As shown, iron sulfide was placed in anhydrous ethanol and ultrasonicated for 2 min before being measured and the particle size distribution of the nanoparticles was calculated using a particle size analyzer. The results showed that the hydrated particle size of the prepared FeS was about 190 nm.

[0037] (4) If Figure 4As shown, FeS was prepared into a concentration gradient solution (100, 50, 25, 12.5 μg / mL) with 2 mL of ethanol and its absorption value was measured with a UV-visible spectrophotometer. The results showed that the prepared FeS showed an absorption curve related to the concentration.

[0038] (5) If Figure 5 As shown, artemisinin was prepared into a concentration gradient solution (500, 250, 125, 62.5, 31.25 μg / mL) using 2 mL of ethanol and its absorption value was measured using a UV-visible spectrophotometer. The results showed that artemisinin exhibited an absorption curve related to concentration (absorption peak 202 nm).

[0039] (6) If Figure 6 As shown, the absorbance value of artemisinin at 202 nm was plotted against the corresponding artemisinin concentration. The results showed that the concentration of artemisinin showed an absorption curve that was positively correlated with the absorbance.

[0040] (7) Figure 7 As shown in the figure, the absorption curves of iron sulfide-PEG (FP), artemisinin (A) and iron sulfide-PEG-artemisinin (FPA) were measured by UV spectrophotometer, and the results showed that artemisinin had an absorption peak at 200 nm due to the electronic transition of the peroxide bridge structure (OO bond) of artemisinin. The absorption peak of iron sulfide at around 204 nm is caused by the electronic transition of the Fe-S bond. The overall absorption curve of the prepared iron sulfide-artemisinin (FeS-PEG-artemisinin) complex is elevated, and the absorption peak is between 200 nm and 204 nm, indicating the successful synthesis of the complex and stable interaction.

[0041] (8) Figure 8 As shown in the figure, FPA was added to the red blood cell suspension, and the final concentrations were 0.78, 1.56, 3.13, 6.25, 12.5, 25, 50, and 100 μg / mL, respectively. The red blood cell suspension diluted with PBS was used as the negative control, and the red blood cell suspension diluted with superfluid was used as the positive control (indicated by (+) in the figure). Each group of solutions was incubated at 37°C for 4 hours, and then the solution was centrifuged at 3000 rpm for 15 minutes. The hemolysis phenomenon was photographed, and the absorbance of the sample at 542 nm was detected by an enzyme marker, and the hemolysis rate was finally calculated. The results showed that when FPA of different concentrations was co-incubated with red blood cells, it can be observed that almost all red blood cells sank, and the supernatant did not change much compared with the negative control group. This shows that the prepared FPA did not cause hemolysis of red blood cells and had good biocompatibility with blood cells.

[0042] (9) Fig. 9 As shown, the activated LX-2 cell line was cultured at 1*10 4 / well were cultured in a 96-well plate and cultured in an incubator containing 5% CO2 for 24 hours. After the cells were stabilized, iron sulfide-PEG (FP), artemisinin (A) and iron sulfide-PEG-artemisinin (FPA) were added in a concentration gradient and incubated with the cells for 24 hours. Thereafter, the culture medium containing the materials was removed, and a culture medium containing 5 mg / ml MTT was added to react for 4 hours. The absorbance of the cells at various concentrations was measured using an ELISA instrument, and the cell survival rate was calculated and plotted. The results showed that with the increase in concentration, the survival rate of LX-2 cells gradually decreased, proving that it had a toxic effect on liver fibrosis cells, and FPA was the most toxic to liver fibrosis cells, proving the synergistic effect of the two.

[0043] (10) Fig.10 As shown, PBS, FP, A, and FPA were incubated with activated LX-2 cells respectively. After 6 hours, the cells were lysed by ultrasound, centrifuged at 8000g and 4°C, and the supernatant was retained. The hydrogen peroxide concentration in the cell suspension was measured using a hydrogen peroxide concentration kit (Solebo, BC3590). The results showed that the concentration of hydrogen peroxide decreased after the addition of FP, A, and FPA, indicating that iron sulfide and artemisinin have certain reducing properties.

[0044] (11) Fig.11 As shown in the figure, FPA (FITC modified) was incubated with activated LLC cells at concentrations of 0 µg / ml, 10 µg / ml, and 40 µg / ml for 4 hours, and the cell uptake of nanomaterials was detected using a fluorescent inverted microscope. The results showed that as the concentration increased, the fluorescence captured by the microscope gradually increased, indicating that the prepared FPA can be effectively taken up by tumor cells in a concentration-dependent manner.

[0045] (12) Fig.12As shown, activated LX-2 cells were treated with PBS, iron sulfide-PEG (FP), artemisinin (A), and iron sulfide-PEG-artemisinin (FPA) for 24 hours. The cells were then scraped and lysed using a cell scraper, and the protein concentration was determined using a BCA protein quantification kit. Subsequently, the proteins were separated by 10% SDS-PAGE and transferred to a PVDF membrane (0.45 μm) for imaging. After blocking with 5% skim milk powder, antibodies against COL-1, Smad4, α-SMA, GAPDH (1:1000-2000), and HRP-labeled goat anti-rabbit secondary antibody (1:5000) were incubated in sequence. Finally, the protein bands were visualized using an ECL detection kit. The results showed that the iron sulfide-PEG-artemisinin (FPA) grouping led to a significant decrease in COL-1, Smad4, and α-SMA, and the expression of the three proteins in the FPA group was significantly lower than that in the iron sulfide-PEG (FP) and artemisinin (A) groups, confirming the synergistic ability of the two drugs and the ability of FPA to treat liver fibrosis.

[0046] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-liver fibrosis nanomedicine, characterized in that: The following steps are involved: 1) Mix ammonium ferrous sulfate, trisodium citrate and ethylene glycol to obtain solution A; 2) mixing the solution A obtained in step 1) with the polyethyleneimine solution to obtain a solution B; 3) mixing the solution B obtained in step 2) with the thioacetamide solution to obtain a solution C; 4) mixing the solution C obtained in step 3) with triethanolamine and reacting the mixture to obtain iron sulfide nanosheets; 5) mixing the iron sulfide nanosheets obtained in step 4) with thiol-polyethylene glycol-amino and anhydrous ethanol to obtain polyethylene glycol-modified iron sulfide nanosheets; 6) Mixing the polyethylene glycol-modified iron sulfide nanosheets obtained in step 5) with artemisinin and anhydrous ethanol to obtain an anti-liver fibrosis nanomedicine.

2. The preparation method according to claim 1, characterized in that: In the step 1), the volume ratio of the mole of ammonium ferrous sulfate, the mole of trisodium citrate and ethylene glycol is 0.6 mmol:0.2 mmol:15 mL.

3. The preparation method according to claim 1, characterized in that: The components of the polyethyleneimine solution in step 2) include polyethyleneimine and ethylene glycol, and the mass ratio of the polyethyleneimine to the volume of ethylene glycol is 500 mg:5 mL; The molar ratio of the volume of the polyethyleneimine solution to the ammonium ferrous sulfate is 5 mL:0.6 mmol; The mixing conditions include: stirring at 500 rpm for 2 hours.

4. The preparation method according to claim 1, characterized in that: The components of the thioacetamide solution in step 3) include thioacetamide and ethylene glycol, and the mass ratio of thioacetamide to ethylene glycol is 56.3475 mg:15 mL; The mixing is carried out under stirring, and the stirring time is 10 minutes; The volume ratio of the thioacetamide solution to the polyethyleneimine solution is 3:

1.

5. The preparation method according to claim 1, characterized in that: In step 4), the volume ratio of triethanolamine to thioacetamide solution is 0.5:15; The mixing is carried out under stirring, and the stirring time is 10 minutes; The reaction conditions include: temperature of 200°C and time of 4h; The reaction is followed by centrifugation and washing to obtain iron sulfide nanosheets; the centrifugation conditions include: a rotation speed of 14000 rpm and a time of 10 minutes; and washing with anhydrous ethanol for 3 times.

6. The preparation method according to claim 1, characterized in that: In the step 5), the volume ratio of the mass of the iron sulfide nanosheets to the mass of the mercapto-polyethylene glycol-amino group and the anhydrous ethanol is 1 mg:1 mg:2 mL.

7. The preparation method according to claim 1, characterized in that: The step 5) mixing is carried out under stirring, and the stirring time is 6 hours; The stirring is followed by centrifugation and washing, wherein the centrifugation conditions include: a rotation speed of 14000 rpm for 10 min; and washing with anhydrous ethanol for 2 times.

8. The preparation method according to claim 1, characterized in that: In step 6), the volume ratio of the mass of the polyethylene glycol-modified iron sulfide nanosheets to the mass of artemisinin and anhydrous ethanol is 1 mg:1 mg:2 mL; The mixing is carried out under stirring, and the stirring time is 6 hours; The stirring is followed by centrifugation and washing, wherein the centrifugation conditions include: a rotation speed of 14000 rpm for 10 min; and washing with anhydrous ethanol for 2 times.

9. A method for preparing an anti-liver fibrosis nanomedicine prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the anti-liver fibrosis nanomedicine according to claim 9 in the preparation of a drug for treating liver fibrosis.

Citation Information

Patent Citations

  • Application of artemisinin derivative in preparing medicine for treating hepatic fibrosis

    CN105878233A

  • Iron carbide nanoparticle loaded artemisinin medicine composite material, and preparation method and application thereof

    CN107670038A

  • Two-dimensional iron sulfide nanosheet as well as preparation method and application thereof

    CN116477668A